UOS / MFI co-crystallized molecular sieve and its preparation method and application and UOS / MFI co-crystallized molecular sieve composition and its application
Through the chemical composition of SiO2·1/x GeO2 and the use of organic template agents, UOS/MFI co-crystalline molecular sieve was prepared, which solved the problems of high synthesis cost and limited application of UOS molecular sieve, and achieved low-cost and high-purity co-crystalline The preparation of molecular sieve and flexible catalytic activity have enhanced its application potential in the field of catalysis.
Patent Information
- Application Number
- CN202111235490.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-22
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2041-10-22
AI Technical Summary
In the existing synthesis methods of UOS molecular sieve, template agents are expensive and have a narrow synthesis range, and the application of co-crystalline molecular sieve in the field of catalysis is limited by the defects of single-channel structure.
UOS/MFI co-crystallation is prepared by mixing the organic template agent 3-diethylamino-1-propanol with silicon, germanium, fluorine and water. Molecular sieve, and the weight percentage of UOS and MFI molecular sieve is adjustable, achieving simple and low-cost synthesis.
It realizes the low-cost and high-purity preparation of UOS/MFI co-crystalline molecular sieve, and has a flexible catalytic activity center, which can be used in different catalytic reactions, which enhances the application prospects of molecular sieve in the catalytic field.
Smart Images

Figure CN116002698B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of molecular sieves, and in particular to a UOS / MFI co-crystallized molecular sieve and a preparation method and application thereof, and a UOS / MFI co-crystallized molecular sieve and application thereof. Background Art
[0002] MFI molecular sieve (US 3,702,886) is a medium-pore molecular sieve whose skeleton consists of two intersecting pore systems, where the opening diameter of the straight cylindrical pore in the
[010] direction is 0.53×0.56nm; the opening diameter of the "Z"-shaped pore in the
[100] direction is 0.51×0.55nm. MFI molecular sieve is widely used in catalytic cracking to increase propylene production and improve gasoline octane number, toluene disproportionation, olefin cracking, benzene alkylation and other catalytic processes.
[0003] UOS molecular sieve is a mesoporous molecular sieve with three-dimensional cross channels, in which the 10-membered ring channel along the a-axis has an opening diameter of 0.36×0.63nm, and the opening diameters of the 8-membered ring channel along the b-axis and c-axis are 0.27×0.35nm and 0.30×0.30nm respectively. The unique channel system of UOS molecular sieve makes it have great application prospects in the fields of adsorption separation and catalytic conversion of organic matter. Researchers from the French Petroleum Research Institute first disclosed the structure and preparation method of UOS molecular sieve in French patent FR07 / 05.315. The template used in the synthesis is 3-ethyl-1-methylimidazolium ion (3-Ethyl-1-methyl-3H-imidazol-1-ium). The main problem of this synthesis method is that the template is expensive and the synthesis range of UOS molecular sieve is narrow.
[0004] Co-crystallized molecular sieves refer to co-crystallizations formed by two or more molecular sieves, or composite crystals with structural characteristics of two or more molecular sieves. Such molecular sieves often have properties different from those of a single molecular sieve or a corresponding mechanical mixture. Since co-crystal molecular sieves have multiple structures and superposition functions, they avoid the defects of a single pore structure system, have great advantages in molecular adsorption and diffusion, and have broad application prospects in the field of oil refining catalysis. Common co-crystallized molecular sieves include ZSM-5 / ZSM-11 (CN 1137022A), MCM-49 / ZSM-35 (Micropro. Mesopro. Mater., 2009, 121, 166-172), BEA / MOR (Chin. J Catal., 2006, 27: 228-232), etc. Summary of the invention
[0005] The present invention aims to provide a UOS / MFI co-crystallized molecular sieve and its preparation method and application. The molecular sieve preparation method is simple, the synthesis cost is low, and the organic template structure is simple and single, and the weight percentage of UOS and MFI molecular sieves in the co-crystallized molecular sieve is adjustable within the range of 1% to 99%.
[0006] In order to achieve the above object, the first aspect of the present invention provides a UOS / MFI co-crystallized molecular sieve, wherein the UOS / MFI co-crystallized molecular sieve has a schematic chemical composition as shown in the formula: SiO2·1 / x GeO2, and preferably the X-ray diffraction pattern of the UOS / MFI co-crystallized molecular sieve includes characteristic peaks as shown in the following table:
[0007]
[0008]
[0009] Among them, the molar ratio of SiO2 to GeO2 is 5.2≤x≤9.8, and the preferred molar ratio of SiO2 to GeO2 is 5.5≤x≤8.5.
[0010] The second aspect of the present invention provides a method for preparing the UOS / MFI co-crystallized molecular sieve, which comprises the steps of: the organic template M is 3-diethylamino-1-propanol, a silicon source, a germanium source, a fluorine source, the organic template M and water are mixed, and a crystallization reaction is carried out to obtain the UOS / MFI co-crystallized molecular sieve.
[0011] A third aspect of the present invention provides a UOS / MFI co-crystallized molecular sieve composition, comprising: the UOS / MFI co-crystallized molecular sieve described in the present invention and a binder.
[0012] A fourth aspect of the present invention provides a use of the UOS / MFI co-crystallized molecular sieve of the present invention or the UOS / MFI co-crystallized molecular sieve composition of the present invention as an adsorbent or catalyst component.
[0013] The method for preparing the UOS / MFI co-crystallized molecular sieve provided by the present invention has the characteristics of a simple and single organic template structure, no need to be carried out under high-speed stirring conditions, and the weight percentage of the UOS and MFI molecular sieves in the co-crystallized molecular sieve is adjustable within the range of 1% to 99%. After the Si and Ge elements in the framework of the UOS / MFI co-crystallized molecular sieve are partially replaced, one or more of the other framework elements except Si and Ge can be introduced into the framework to generate different catalytic active centers to meet the needs of different catalytic reactions. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1is the X-ray diffraction (XRD) pattern of the sample obtained in Example 1;
[0015] Figure 2 This is a scanning electron microscope (SEM) image of the sample obtained in Example 1;
[0016] Figure 3 is the X-ray diffraction (XRD) pattern of the sample obtained in Example 2;
[0017] Figure 4 This is a scanning electron microscope (SEM) image of the sample obtained in Example 2. DETAILED DESCRIPTION
[0018] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0019] According to the first aspect of the present invention, the present invention provides a UOS / MFI co-crystallized molecular sieve, wherein the UOS / MFI co-crystallized molecular sieve has a schematic chemical composition as shown in the formula: SiO2·1 / x GeO2, and preferably the X-ray diffraction pattern of the UOS / MFI co-crystallized molecular sieve includes characteristic peaks as shown in the following table:
[0020]
[0021] Among them, the molar ratio of SiO2 to GeO2 is 5.2≤x≤9.8, and the preferred molar ratio of SiO2 to GeO2 is 5.5≤x≤8.5.
[0022] The data in the above table represent the interplanar spacing of the UOS / MFI co-crystallized molecular sieve at 2θ(°) of 7.84±0.2. It is 11.27±0.55, and so on. The representation method of this table is well known to those skilled in the art, and the present invention will not explain them one by one here.
[0023] According to a preferred embodiment of the present invention, in the UOS / MFI co-crystallized molecular sieve, the weight percentage of UOS molecular sieve is 1% to 99%, and the weight percentage of MFI molecular sieve is 1% to 99%; the weight percentage of UOS and MFI molecular sieves in the co-crystallized molecular sieve of the present invention is adjustable within the range of 1% to 99%. Preferably, the weight percentage of UOS molecular sieve is 5% to 95%, and the weight percentage of MFI molecular sieve is 5% to 95%.
[0024] In the present invention, the content of each molecular sieve in the UOS / MFI co-crystallized molecular sieve is obtained by measuring the relative proportion of the sum of its characteristic diffraction peak areas to the sum of all diffraction peak areas.
[0025] According to the present invention, after the Si and Ge elements in the UOS / MFI co-crystallized molecular sieve framework are partially replaced, one or more of other framework elements (such as non-silicon tetravalent framework elements and / or trivalent framework elements) other than Si and Ge can be introduced into the framework to produce different catalytic active centers to meet the needs of different catalytic reactions. Preferably, no more than 10wt% of Si atoms in the UOS / MFI co-crystallized molecular sieve are replaced by at least one non-silicon tetravalent framework element Y; preferably, 1 to 9wt% of Si atoms in the UOS / MFI co-crystallized molecular sieve are replaced by at least one non-silicon tetravalent framework element Y; more preferably, the Y is selected from at least one of tin, titanium, zirconium and hafnium.
[0026] According to a preferred embodiment of the present invention, no more than 15wt% of the Ge atoms in the UOS / MFI co-crystallized molecular sieve are substituted by at least one trivalent framework element X; preferably, 2-12wt% of the Ge atoms in the UOS / MFI co-crystallized molecular sieve are substituted by at least one trivalent framework element X; more preferably, X is selected from at least one of aluminum, boron, iron, gallium, indium and chromium.
[0027] According to a preferred embodiment of the present invention, the morphologies of the UOS / MFI co-crystallized molecular sieve include: flaky UOS molecular sieve morphology and "coffin-shaped" MFI molecular sieve morphology.
[0028] The UOS / MFI co-crystallized molecular sieves with the above characteristics can achieve the purpose of the present invention, and there is no special requirement for their preparation methods. The present invention provides a method for preparing the UOS / MFI co-crystallized molecular sieve, which comprises: the organic template M is 3-diethylamino-1-propanol, a silicon source, a germanium source, a fluorine source, an organic template M and water are mixed, and a crystallization reaction is performed to obtain the UOS / MFI co-crystallized molecular sieve. The preparation method of the UOS / MFI co-crystallized molecular sieve of the present invention is simple and has a low synthesis cost; the preparation method has the characteristics of a single and simple organic template structure, and the weight percentage of the UOS and MFI molecular sieves in the co-crystallized molecular sieve is adjustable within the range of 1% to 99%. After partially replacing the Si and Ge elements in the framework, one or more of the other framework elements other than Si and Ge, such as non-silicon tetravalent framework elements and / or trivalent framework elements, can also be introduced into the framework to produce different catalytic active centers to meet the needs of different catalytic reactions.
[0029] According to a preferred embodiment of the present invention, the molar ratio of the organic template M, the silicon source calculated as SiO2, the germanium source calculated as GeO2, the fluorine source calculated as F and water is M:SiO2: GeO2:F:H2O=0.15~4:1:0.102~0.192:0.2~4:5~35; preferably M:SiO2:GeO2:F: H2O=0.5~2:1:0.118~0.182:0.35~2.5:10~30.
[0030] According to a preferred embodiment of the present invention, the silicon source is at least one selected from the group consisting of water glass, silica sol, solid silica gel, fumed silica, amorphous silica, diatomaceous earth, zeolite molecular sieve and tetraalkoxysilane.
[0031] According to a preferred embodiment of the present invention, the germanium source is selected from at least one of germanium oxide, germanium nitrate and tetraalkoxygermanium.
[0032] According to a preferred embodiment of the present invention, the fluorine source is selected from at least one of hydrofluoric acid, ammonium fluoride, sodium fluoride and potassium fluoride, preferably at least one of hydrofluoric acid and ammonium fluoride.
[0033] According to a preferred embodiment of the present invention, the crystallization reaction conditions include crystallization at 100-200° C. for 24-300 hours; preferably crystallization at 110-190° C. for 36-250 hours, and more preferably crystallization at 160-180° C. for 100-210 hours.
[0034] According to a preferred embodiment of the present invention, the crystallization is carried out under static and / or dynamic conditions, preferably the crystallization is carried out under static conditions, and the preparation method of the UOS / MFI co-crystallized molecular sieve provided by the present invention has the advantages of simple organic template structure and high product purity can be obtained without high-speed stirring. In the present invention, the results of static or dynamic crystallization remain basically the same, and the embodiments of the present invention do not specifically describe static or dynamic.
[0035] According to a preferred embodiment of the present invention, the mixing is carried out in the presence of a non-silicon tetravalent framework element Y source and / or a trivalent framework element X source, the molar ratio of the non-silicon tetravalent framework element Y source calculated as the corresponding oxide YO2 to the silicon source calculated as SiO2 is YO2 / SiO2=0~0.1, preferably YO2 / SiO2=0.01~0.09; the molar ratio of the trivalent framework element X source calculated as the corresponding oxide X2O3 to the germanium source calculated as GeO2 is X2O3 / GeO2=0~0.075, preferably X2O3 / GeO2=0.01~0.06.
[0036] According to a preferred embodiment of the present invention, the tin source is selected from at least one of tin tetrachloride, stannous chloride, alkyl tin, alkoxy tin and organic tin esters; the titanium source is selected from at least one of tetraalkyl titanates (such as tetramethyl titanate, tetraethyl titanate, tetrapropyl titanate, tetra-n-butyl titanate), titanium tetrachloride, hexafluorotitanic acid, titanium sulfate and their hydrolyzates; the zirconium source and hafnium source are selected from conventional substances in the art, such as zirconium nitrate, zirconium oxychloride, hafnium sulfate, etc.
[0037] According to a preferred embodiment of the present invention, the aluminum source is selected from at least one of aluminum sulfate, sodium aluminate, aluminum nitrate, aluminum chloride, pseudo-boehmite, aluminum oxide, aluminum hydroxide, silica-aluminum zeolite molecular sieve, aluminum carbonate, elemental aluminum, aluminum isopropoxide and aluminum acetate; the boron source is selected from at least one of boric acid, sodium tetraborate, amorphous boron oxide, potassium borate, sodium metaborate, ammonium tetraborate and organic boron esters; the iron source is selected from at least one of ferric sulfate, ferric nitrate, iron halide (such as ferric chloride), ferrocene and ferric citrate; the gallium source, indium source and chromium source are selected from conventional substances in the art, such as gallium oxide, gallium nitrate, indium oxide, indium nitrate, chromium chloride and chromium nitrate, etc.
[0038] According to the present invention, preferably, after the crystallization reaction is completed, conventional post-treatment is performed, such as filtering, washing, and drying to obtain the molecular sieve; and optionally, a step of calcining the obtained molecular sieve.
[0039] The present invention provides a UOS / MFI co-crystallized molecular sieve composition, which comprises: the UOS / MFI co-crystallized molecular sieve described in the present invention and a binder.
[0040] The present invention has no particular limitation on the binder, and any binder in the art can be used as the binder described in the present invention.
[0041] A fourth aspect of the present invention provides a use of the UOS / MFI co-crystallized molecular sieve of the present invention or the UOS / MFI co-crystallized molecular sieve composition of the present invention as an adsorbent or catalyst component.
[0042] In the context of this specification, the structure of the molecular sieve is determined by an X-ray diffraction spectrum (XRD), which is measured by an X-ray powder diffractometer using a Cu-Kα ray source with a Kα1 wavelength of λ=1.5405980 angstroms. Nickel filter.
[0043] In the present invention, an X'Pert PRO X-ray powder diffraction (XRD) instrument of PANalytical Company of the Netherlands is used, with an operating voltage of 40 kV, a current of 40 mA, and a scanning range of 5 to 40°. The product morphology is photographed using an S-4800 field emission scanning electron microscope (Fe-SEM) of HITACHI Company of Japan.
[0044] It should be particularly noted that two or more aspects (or implementation methods) disclosed in the context of this specification can be arbitrarily combined with each other, and the technical solutions (such as methods or systems) thus formed are part of the original disclosure of this specification and also fall within the scope of protection of the present invention.
[0045] Unless otherwise specified, all percentages, parts, ratios, etc. mentioned in this specification are based on weight, unless the weight basis does not conform to the common understanding of those skilled in the art.
[0046] Example 1
[0047] Mix 5.35g 3-diethylamino-1-propanol (DEAP) and 11g water evenly, add 0.65g germanium oxide, and slowly add 5.12g Ludox silica sol (SiO2 40wt%) under stirring after dissolving, continue stirring at room temperature for 3h, and finally add 2g hydrofluoric acid (40wt%), continue stirring for 1 hour, then put the above mixture into a crystallization kettle with polytetrafluoroethylene lining, and place it in a 170℃ oven for crystallization for 168 hours. After the reaction, the solid is filtered, washed with distilled water, and dried at 100℃ to obtain the original powder solid, which is placed in a muffle furnace and calcined at 550℃ for 5 hours to obtain the final product. The XRD spectrum is as follows Figure 1 As shown by Figure 1 It can be seen that the product is a UOS / MFI co-crystallized molecular sieve, in which the UOS molecular sieve content is 50%. The spectrum data is shown in Table 1, and the SEM image is shown in Figure 2 As shown by Figure 2 It can be seen that the product contains both UOS molecular sieve flake crystals and MFI molecular sieve "coffin-shaped" crystals. The composition of the raw materials for synthesizing the molecular sieve is shown in Table 5.
[0048] Table 1
[0049]
[0050]
[0051] Example 2
[0052] Mix 4.73g 3-diethylamino-1-propanol (DEAP) and 8.6g water evenly, add 0.47g germanium oxide, and slowly add 5.4g Ludox silica sol (SiO2 40wt%) under stirring after dissolving, continue stirring at room temperature for 3h, and finally add 1.8g hydrofluoric acid (40wt%), continue stirring for 1 hour, then put the above mixture into a crystallization kettle with a polytetrafluoroethylene liner, and place it in a 175℃ oven for crystallization for 144 hours. The solid after the reaction is filtered, washed, dried, and calcined to obtain the final product. The XRD spectrum is as follows Figure 3 As shown by Figure 3 It can be seen that the product is a UOS / MFI co-crystallized molecular sieve, in which the UOS molecular sieve content is 35%. The spectrum data is shown in Table 2, and the SEM photo is shown in Figure 4 As shown by Figure 4 It can be seen that the product contains both UOS molecular sieve flake crystals and MFI molecular sieve "coffin-shaped" crystals. The composition of the raw materials for synthesizing the molecular sieve is shown in Table 5.
[0053] Table 2
[0054]
[0055]
[0056] Example 3
[0057] Mix 7.9g 3-diethylamino-1-propanol (DEAP) and 2.5g water evenly, add 0.49g germanium oxide, and slowly add 5.3g Ludox silica sol (SiO2 40wt%) under stirring after dissolution, continue stirring at room temperature for 3h, and finally add 6g ammonium fluoride aqueous solution (37wt%). After stirring for 1 hour, the above mixture is placed in a crystallization kettle with a polytetrafluoroethylene liner and placed in a 165℃ oven for crystallization for 156 hours. After the reaction, the solid is filtered, washed, dried, and calcined to obtain the final UOS / MFI co-crystallized molecular sieve product, in which the UOS molecular sieve content is 25%. XRD spectrum and Figure 1 The composition of the raw materials for synthesizing the molecular sieve is shown in Table 5.
[0058] Example 4
[0059] Mix 6.8g 3-diethylamino-1-propanol (DEAP) and 8.2g water evenly, add 0.6g germanium oxide, and slowly add 1.6g Ludox silica sol (SiO2 40wt%) and 1.5g white carbon black (SiO2 95wt%) under stirring after dissolution, continue stirring at room temperature for 3h, and finally add 3.4g hydrofluoric acid (40 wt%). After stirring for 1 hour, the above mixture is placed in a crystallization kettle with a polytetrafluoroethylene liner and placed in a 170°C oven for crystallization for 120 hours. The solid after the reaction is filtered, washed, dried, and calcined to obtain the final UOS / MFI co-crystallized molecular sieve product, in which the UOS molecular sieve content is 60%. XRD spectrum and Figure 1 The composition of the raw materials for synthesizing the molecular sieve is shown in Table 5.
[0060] Example 5
[0061] 4.6g 3-diethylamino-1-propanol (DEAP) was mixed with 4.4g water, and 0.56g germanium oxide was added. After dissolving, 2g Ludox silica sol (SiO2 40wt%) and 1.36g white carbon black (SiO2 95wt%) were slowly added under stirring, and stirring was continued for 3h at room temperature. Finally, 2g hydrofluoric acid (40 wt%) and 1.2g ammonium fluoride aqueous solution (37wt%) were added. After stirring for 1 hour, the above mixture was charged into a crystallization kettle with a polytetrafluoroethylene liner and placed in a 160°C oven for crystallization for 192 hours. After the reaction, the solid was filtered, washed, dried and calcined to obtain the final UOS / MFI co-crystallized molecular sieve product, wherein the UOS molecular sieve content was 40%. The XRD spectrum data are shown in Table 3. The composition of the raw materials for synthesizing the molecular sieve is shown in Table 5.
[0062] Table 5
[0063]
[0064]
[0065] Example 6
[0066] Mix 6.6g 3-diethylamino-1-propanol (DEAP) and 11.8g water evenly, add 0.44g germanium oxide, and slowly add 1.8g Ludox silica sol (SiO2 40wt%) and 1.5g white carbon black (SiO2 95wt%) under stirring after dissolution, continue stirring at room temperature for 3h, and finally add 1g hydrofluoric acid (40 wt%) and 1.2g ammonium fluoride aqueous solution (37wt%). After stirring for 1 hour, the above mixture is placed in a crystallization kettle with a polytetrafluoroethylene liner and placed in an oven at 180°C for crystallization for 108 hours. The solid after the reaction is filtered, washed, dried, and calcined to obtain the final UOS / MFI co-crystallized molecular sieve product, in which the UOS molecular sieve content is 20%. XRD spectrum and Figure 1 The composition of the raw materials for synthesizing the molecular sieve is shown in Table 5.
[0067] Example 7
[0068] 5.35g 3-diethylamino-1-propanol (DEAP) was mixed with 11g water, 0.65g germanium oxide and 0.17g aluminum sulfate 18 hydrate were added, and 5.12g Ludox silica sol (SiO2 40wt%) was slowly added under stirring after dissolution, and stirring was continued for 3h at room temperature, and finally 2g hydrofluoric acid (40wt%) was added, and stirring was continued for 1 hour, and the above mixture was charged into a crystallization kettle with a polytetrafluoroethylene liner, and placed in a 160°C oven for crystallization for 204 hours. After the reaction, the solid was filtered, washed, dried, and calcined to obtain the final Al-UOS / MFI co-crystallized molecular sieve product, wherein the UOS molecular sieve content was 55%. The XRD spectrum data are shown in Table 4. The composition of the raw materials for synthesizing the molecular sieve is shown in Table 5.
[0069] Table 4
[0070]
[0071]
[0072] Example 8
[0073] Mix 5.35g 3-diethylamino-1-propanol (DEAP) and 11g water evenly, add 0.65g germanium oxide and 0.04g boric acid, and slowly add 5.12g Ludox silica sol (SiO2 40 wt%) and 0.29g tetrabutyl titanate under stirring after dissolution, continue stirring at room temperature for 3h, and finally add 2g hydrofluoric acid (40 wt%), continue stirring for 1 hour, then put the above mixture into a crystallization kettle with a polytetrafluoroethylene liner, and place it in a 175℃ oven for crystallization for 132 hours. After the reaction, the solid is filtered, washed, dried, and calcined to obtain the final B-Ti-UOS / MFI co-crystallized molecular sieve product, in which the UOS molecular sieve content is 70%. XRD spectrum and Figure 1 The composition of the raw materials for synthesizing the molecular sieve is shown in Table 5.
[0074] Example 9
[0075] 5.35g 3-diethylamino-1-propanol (DEAP) was mixed with 11g water, 0.65g germanium oxide and 0.29g aluminum sulfate 18 hydrate were added, and 5.12g Ludox silica sol (SiO2 40wt%) was slowly added under stirring after dissolution, and stirring was continued for 3h at room temperature, and finally 2g hydrofluoric acid (40wt%) was added, and stirring was continued for 1 hour, and the above mixture was loaded into a crystallization kettle with a polytetrafluoroethylene liner, and placed in a 160°C oven for crystallization for 204 hours. After the reaction, the solid was filtered, washed, dried, and calcined to obtain the final Al-UOS / MFI co-crystallized molecular sieve product, wherein the UOS molecular sieve content was 48%. The raw material composition of the synthesized molecular sieve is shown in Table 5.
[0076] Example 10
[0077] Mix 5.35g 3-diethylamino-1-propanol (DEAP) and 11g water evenly, add 0.65g germanium oxide, 0.05g boric acid and 0.64g titanium sulfate, and slowly add 5.12g Ludox silica sol (SiO2 40wt%) and continue stirring at room temperature for 3h, and finally add 2g hydrofluoric acid (40 wt%), continue stirring for 1 hour, then put the above mixture into a crystallization kettle with a polytetrafluoroethylene liner, and place it in a 175℃ oven for crystallization for 132 hours. After the reaction, the solid is filtered, washed, dried and calcined to obtain the final B-Ti-UOS / MFI co-crystallized molecular sieve product, in which the UOS molecular sieve content is 30%. XRD spectrum and Figure 2 The composition of the raw materials for synthesizing the molecular sieve is shown in Table 5.
[0078] Table 5 Molecular sieve raw material molar ratio composition of Examples 1-10
[0079] project <![CDATA[SiO2 / GeO2]]> <![CDATA[M / SiO2]]> F / Si <![CDATA[H2O / Si]]> <![CDATA[YO2 / SiO2]]> <![CDATA[X2O3 / GeO2]]> Example 1 5.5 1.2 1.2 25 0 0 Example 2 8 1 1 20 0 0 Example 3 7.5 1.7 1.7 15 0 0 Example 4 6 1.5 2.0 18 0 0 Example 5 6.5 1 1.5 12 0 0 Example 6 8.5 1.4 0.9 22 0 0 Example 7 5.5 1.2 1.2 25 0 0.04 Example 8 5.5 1.2 1.2 25 0.025 0.05 Example 9 5.5 1.2 1.2 25 0 0.07 Example 10 5.5 1.2 1.2 25 0.092 0.065
[0080] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A UOS / MFI cocrystallized molecular sieve, characterized in that: The UOS / MFI co-crystallized molecular sieve has a schematic chemical composition as shown in the formula: SiO2·1 / x GeO2, wherein the molar ratio of SiO2 to GeO2 is 5.2≤x≤9.8; The X-ray diffraction spectrum of the UOS / MFI co-crystallized molecular sieve includes characteristic peaks as shown in the following table:
2. The UOS / MFI co-crystallized molecular sieve according to claim 1, wherein The molar ratio of SiO2 to GeO2 is 5.5≤x≤8.
5.
3. The UOS / MFI co-crystallized molecular sieve according to claim 1 or 2, wherein: In the UOS / MFI co-crystallized molecular sieve, the weight percentage of the UOS molecular sieve is 1% to 99%, and the weight percentage of the MFI molecular sieve is 1% to 99%.
4. The UOS / MFI co-crystallized molecular sieve according to claim 3, wherein: In the UOS / MFI co-crystallized molecular sieve, the weight percentage of the UOS molecular sieve is 5% to 95%, and the weight percentage of the MFI molecular sieve is 5% to 95%.
5. The UOS / MFI co-crystallized molecular sieve according to claim 1 or 2, wherein: No more than 10 wt% of Si atoms in the UOS / MFI co-crystallized molecular sieve are replaced by at least one non-silicon tetravalent framework element Y.
6. The UOS / MFI co-crystallized molecular sieve according to claim 5, wherein: 1-9wt% of Si atoms in the UOS / MFI co-crystallized molecular sieve are replaced by at least one non-silicon tetravalent skeleton element Y.
7. The UOS / MFI co-crystallized molecular sieve according to claim 5, wherein The Y is selected from at least one of tin, titanium, zirconium and hafnium.
8. The UOS / MFI co-crystallized molecular sieve according to claim 1 or 2, wherein: No more than 15 wt % of the Ge atoms in the UOS / MFI co-crystallized molecular sieve are substituted by at least one trivalent framework element X.
9. The UOS / MFI co-crystallized molecular sieve according to claim 8, wherein: 2-12 wt% of the Ge atoms in the UOS / MFI co-crystallized molecular sieve are replaced by at least one trivalent framework element X.
10. The UOS / MFI co-crystallized molecular sieve according to claim 8, wherein: The X is selected from at least one of aluminum, boron, iron, gallium, indium and chromium.
11. The UOS / MFI co-crystallized molecular sieve according to claim 1 or 2, wherein: The morphologies of the UOS / MFI co-crystallized molecular sieve include: flaky UOS molecular sieve morphology and "coffin-shaped" MFI molecular sieve morphology.
12. A method for preparing the UOS / MFI cocrystallized molecular sieve according to any one of claims 1 to 11, characterized in that: The method comprises the steps of: the organic template M is 3-diethylamino-1-propanol, a silicon source, a germanium source, a fluorine source, the organic template M and water are mixed, and a crystallization reaction is performed to obtain a UOS / MFI co-crystallized molecular sieve.
13. The preparation method according to claim 12, wherein: The molar ratio of the organic template M, the silicon source calculated as SiO2, the germanium source calculated as GeO2, the fluorine source calculated as F and water is M: SiO2: GeO2: F: H2O = 0.15~4: 1: 0.102~0.192: 0.2~4: 5~35.
14. The preparation method according to claim 13, wherein: The molar ratio of the organic template M, the silicon source calculated as SiO2, the germanium source calculated as GeO2, the fluorine source calculated as F and water is M: SiO2: GeO2: F: H2O = 0.5~2: 1: 0.118~0.182: 0.35~2.5: 10~30.
15. The preparation method according to any one of claims 12 to 14, wherein: The silicon source is at least one selected from the group consisting of water glass, silica sol, solid silica gel, fumed silica, amorphous silica, diatomaceous earth, zeolite molecular sieve and tetraalkoxysilane.
16. The preparation method according to any one of claims 12 to 14, wherein: The germanium source is selected from at least one of germanium oxide, germanium nitrate and tetraalkoxygermanium.
17. The preparation method according to any one of claims 12 to 14, wherein: The fluorine source is selected from at least one of hydrofluoric acid, ammonium fluoride, sodium fluoride and potassium fluoride.
18. The preparation method according to any one of claims 12 to 14, wherein: The fluorine source is selected from at least one of hydrofluoric acid and ammonium fluoride.
19. The preparation method according to any one of claims 12 to 14, wherein: The conditions of the crystallization reaction include crystallization at 100-200°C for 24-300 hours.
20. The preparation method according to claim 19, wherein: The conditions of the crystallization reaction include crystallization at 110-190°C for 36-250 hours.
21. The preparation method according to claim 19, wherein The conditions of the crystallization reaction include crystallization at 160-180° C. for 100-210 hours.
22. The preparation method according to any one of claims 12 to 14, wherein: The crystallization is performed under static and / or dynamic conditions.
23. The preparation method according to any one of claims 12 to 14, wherein: The mixing is carried out in the presence of a non-silicon tetravalent skeleton element Y source and / or a trivalent skeleton element X source, The molar ratio of the non-silicon tetravalent skeleton element Y source calculated as the corresponding oxide YO2 to the silicon source calculated as SiO2 is YO2 / SiO2=0~0.
1.
24. The preparation method according to claim 23, wherein: The molar ratio of the non-silicon tetravalent skeleton element Y source calculated as the corresponding oxide YO2 to the silicon source calculated as SiO2 is YO2 / SiO2=0.01~0.
09.
25. The preparation method according to claim 23, wherein: The molar ratio of the trivalent skeleton element X source calculated as the corresponding oxide X2O3 to the germanium source calculated as GeO2 is X2O3 / GeO2=0-0.
075.
26. The preparation method according to claim 23, wherein The molar ratio of the trivalent skeleton element X source calculated as the corresponding oxide X2O3 to the germanium source calculated as GeO2 is X2O3 / GeO2=0.01-0.
06.
27. A UOS / MFI co-crystallized molecular sieve composition, characterized in that: The composition comprises: the UOS / MFI co-crystallized molecular sieve according to any one of claims 1 to 11 and a binder.
28. Use of the UOS / MFI co-crystallized molecular sieve according to any one of claims 1 to 11 or the UOS / MFI co-crystallized molecular sieve composition according to claim 27 as an adsorbent or catalyst component.
